(Nc)QÆLÆSNIJ PÆDHÆD U PSIHOLOGÆÇ OSOBISTOSTÆ(B: (NOSOBLIWOSTÆ TEORÆÇ TA PRAKTIKI (B:s)E (NMATER)QÆALI ææ mÆVNARODNOÇ NAUKOWO(B-(NPRAKTI^NOÇ ONLAJN KONFERENCÆÇ (B(25 (NL@TOGO (B2022 (NROKU(B) : (NZBÆRNIK TEZ (B/s)E - (NkLO^EK(B, (Nl(B. (Nw(B.,s; (NgEJKO(B, )Qã. (Nw(B.,s)E; (NcENTRALXNOUKRA)QÇNSXKIJ DERVAWNIJ PEDAGOGÆ^NIJ UNÆWERSITET ÆMENÆ wOLODIMIRA wINNI^ENKAs)E; (NnAC)QÆONALXNA AKADEMÆQ PEDAGOGÆ^NIH NAUK uKRAÇNIs)E )Qæ(NNSTITUT PSIHOLOGÆÇ ÆMENÆ g(B.(Ns(B. (NkOST@KA napn uKRAÇNIs)E; (Ntow wI]IJ NAW^ALXNIJ ZAKLAD m)QÆLENÆUMs)E; (NwI]A L)QÆNGWÆSTI^NA [KOLA (B((N~ENSTOHOWA(B)s)E; Colláege International de Techniques d'Activation de la Conscience; (NkREATIWNA [KOLA UN)QÆWERSITETU rAJÃRSON(B((NtORONTO(B)s)E; (NtA[KENTSXKIJ DERVAWNIJ PEDAGOG)QÆ^NIJ UNÆWERSITET ÆM(B. (NnÆZAMÆs)E; (NbUHARSXKIJ DERVAWNIJ UN)QÆWERSITETs)E ((NkROPIWNICXKIJ (B:s (Ncdpu(B,s, 2022)
(Nu ZB)QÆRCÆ PREDSTAWLENÆ TEZI DOPOWÆDEJ U^ASNIKÆW ææ mÆVNARODNOÇ NAUKOWO(B-(NPRAKTI^NOÇ ONLAJN KONFERENCÆÇ (S0(NcÆLÆSNIJ PÆDHÆD U PSIHOLOGÆÇ OSOBISTOSTÆ(B: (NOSOBLIWOSTÆ TEORÆÇ TA PRAKTIKI(S1(B. (NwISWÆTL@@TXSQ AKTUALXNÆ PROBLEMI TEORÆÇ(B, (NMETODIKI TA PRAKTIKI PSIHOLOGÆÇ STANOWLENNQ OSOBISTOSTÆ W SU^ASNOMU SUSPÆLXSTWÆ(B.s)E
Improving relevance of teaching and learning in higher education institutions as a current issue of psychological science and practice 186-187; (NpOKLAD )Qæ(B. (NwPLIW SOCÆOKULXTURNIH ^INNIKÆW NA FORMUWANNQ TA ROZWITOK TWOR^OÇ OSOBISTOSTÆ (B188-193; (NmOL^ANOWA o(B. (NmOVLIWOSTÆ ARTTERAPÆÇ DLQ ROZWITKU PEDAGOGÆKI PARTNERSTWA (B194-197; (NkOTLOWA l(B. (NpSIHOLOGÆ^NA MOTIWACÆQ MAJBUTNÆH PEDAGOGÆW(B-(NLOGOPEDÆW DO PROFESÆJNOÇ DÆQLXNOSTÆ (B198-199; (NpRISQVN@K o(B. (NwRAHUWANNQ PSIHOFÆZÆOLOGÆ^NIH OSOBLIWOSTEJ SPRIJNQTTQ ÆNFORMACÆÇ KORISTUWA^AMI PRI ROZROBCÆ ÆNTERFEJSÆW WEB PRODUKTÆW (B200-201; (NkALA[NIKOWA l(B. (NdÆALOGÆ^NA WZAÃMODÆQ QK EFEKTIWNA ÆNNOWACÆJNA TEHNOLOGÆQ PROFESÆJNOÇ PÆDGOTOWKI MAJBUTNÆH PSIHOLOGÆW (B202-206; (NmUDRIK o(B. (NwIKORISTANNQ NABORU Z [ESTI CEGLINOK (BLEGO (NDLQ REALÆZACÆÇ PÆDHODU (B"(NnAW^ANNQ ^EREZ GRU(B" 207-209;s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NpSIHOLOG)QÆQs)E -- (NrOZWITOK OSOBISTOST)QÆs)E